2019
DOI: 10.3847/1538-4357/aafa1c
|View full text |Cite
|
Sign up to set email alerts
|

The Precious Set of Radio-optical Reference Frame Objects in the Light of Gaia DR2 Data

Abstract: We investigate a sample of 3413 International Celestial Reference Frame (ICRF3) extragalactic radio-loud sources with accurate positions determined by VLBI in the S/X band, mostly active galactic nuclei (AGN) and quasars, which are cross-matched with optical sources in the second Gaia data release (Gaia DR2). The main goal of this study is to determine a core sample of astrometric objects that define the mutual orientation of the two fundamental reference frames, the Gaia (optical) and the ICRF3 (radio) frames… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
(35 reference statements)
1
29
0
Order By: Relevance
“…In the Gaia DR1, there were only a small percentage of sources with normalized arc lengths >3 (Mignard et al 2016;Petrov & Kovalev 2017a). In the Gaia DR2, the fraction of these sources increases to more than 10% (Petrov & Kovalev 2017b;Gaia Collaboration 2018b;Petrov et al 2019;Makarov et al 2019). By deselecting objects mostly based on the optical properties, Makarov et al (2019) still found that 20% of the sources had normalized arc lengths >3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Gaia DR1, there were only a small percentage of sources with normalized arc lengths >3 (Mignard et al 2016;Petrov & Kovalev 2017a). In the Gaia DR2, the fraction of these sources increases to more than 10% (Petrov & Kovalev 2017b;Gaia Collaboration 2018b;Petrov et al 2019;Makarov et al 2019). By deselecting objects mostly based on the optical properties, Makarov et al (2019) still found that 20% of the sources had normalized arc lengths >3.…”
Section: Introductionmentioning
confidence: 99%
“…In the Gaia DR2, the fraction of these sources increases to more than 10% (Petrov & Kovalev 2017b;Gaia Collaboration 2018b;Petrov et al 2019;Makarov et al 2019). By deselecting objects mostly based on the optical properties, Makarov et al (2019) still found that 20% of the sources had normalized arc lengths >3. The factors causing these position differences between A&A 647, A189 (2021) optical and radio are still uncertain, even though there are a variety of possible astrophysical explanations (Makarov et al 2019;Plavin et al 2019a;Kovalev et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience in comparing astrometry at different wavelengths has been gained from cross matching the optical Gaia-CRF and the radio ICRF2/ICRF3. The socalled radio-optical offsets have been detected and are being extensively discussed in the literature [16,150]. Although these offsets are very important for the discussion of individual objects, they are significant for a small fraction of sources and also uncorrelated from one source to another.…”
Section: Maintenance Of the Celestial Reference Framementioning
confidence: 99%
“…Karbon & Nothnagel (2019) compared several radio source position catalogues with Gaia DR2 and used X > 4.2 following Mayer (2018). Makarov et al (2019) compared ICRF3 and Gaia CRF2 and used X > 4 and X > 3 criteria. Liu et al (2020) compared ICRF1, ICRF2 and ICRF3 with Gaia CRF2 using two criteria: X > X0 = √ 2 ln N , where N is the number of sources, and D > 10 mas.…”
Section: Introductionmentioning
confidence: 99%